Effect of Career Adaptability and Career Competencies on Self-Perceived Employability with Mediator Subjective Career Success Variables on Milenial Employees - Dwicahyani, Nastiti; Hadi, Cholichul; Suhariadi, Fendy (Budapest International Research and Critics University, 2022)
This study aims to test whether there is an influence of career adaptability and career competencies on self-perceived employability with mediator variables subjective career success in millennial generation employees. Where the current research is carried out on the subject of millennial generation employees because the largest productive age of workers today is the millennial generation. A quantitative approach was used in this study, with a survey method to collect questionnaire data. The subjects in this study were millennial generation employees who actively worked in a company with a total of 209 respondents. Hypothesis testing was carried out using the Partial Least Square test with the help of Smart PLS 3.0 software.